Comparative Proteomic Analysis by Isobaric Tags for the Relative and Absolute Quantification Reveals the Responses of Tobacco (Nicotiana tabacum L.) Roots to Different Soil Types - Li, Jialiang; Yang, Rui; Jiang, Yonglei; Sun, Shubin; Li, Junying; Gu, Hao; Lin, Ying; Luo, Xianxue; He, Chenggang; Chen, Yi (Frontiers in Plant Science, 2022)
Tobacco (Nicotiana tobacum) root is one of the important organs of tobacco, which affects the yield and quality of tobacco leaves. To gain insight the response of tobacco root system to different types of soil, we integrated morphological characteristics, physiological index, metabolic pathway of root system and aboveground biomass of tobacco cultivated in limestone soil, paddy soil and red soil, respectively. Compared with which in limestone soil and paddy soil, the chemical composition of tobacco leaves in red soil tended to be coordinated. Red soil is beneficial to the accumulation of aboveground and underground biomass of flue-cured tobacco; it had the most significant effect on the dry matter quality of flue-cured tobacco roots; it is beneficial to increase the root length, root surface area, root volume and the number of root forks of flue-cured tobacco, and resulted in greatest morphological characteristics of tobacco roots; it is beneficial to improve the root activity and NR activity of flue-cured tobacco, while the activities of SOD and POD are decreased. We studied differentially expressed proteins between flue-cured tobacco roots cultivated in different types of soils by isobaric tags for relative and absolute quantification (iTRAQ) for the proteomic profiles of cultivar. In total, 699, 650, 569 differentially expressed proteins (DEPs) were identified from limestone soil (LS) vs paddy soil (PS), LS vs red soil (RS), PS vs RS, respectively, including 412/287, 291/359, and 323/246 up/down proteins, respectively. These DEPs were mainly involved in starch and sucrose metabolism, phenylalanine metabolism, biosynthesis of secondary metabolites, microbial metabolism in different environments, and ribosomes. PRM and qRT- PCR analysis showed that the result of iTRAQ proteomics is reliable. Our study provided a new understanding of the response of tobacco roots to different soil types at the protein level.